Manometric Esophageal Length to Height (MELH) Ratio Predicts Hiatal Hernia Recurrence. Issue 6 (July 2020) - Lal, Pooja; Tang, Andrew; Sarvepalli, Shashank; Raja, Siva; Thota, Prashanthi; Lopez, Rocio; Murthy, Sudish; Ray, Monica; Gabbard, Scott
Abstract : Introduction: The shortened esophagus is poorly defined and is determined intraoperatively, as there exists no objective test to identify a shortened esophagus before surgical hiatal hernia repair. We devised a unique manometric esophageal length to height (MELH) ratio to define the presence of a shortened esophagus and examined the role of esophageal length in hiatal hernia recurrence. Patients and Methods: A retrospective review identified 254 patients with hiatal hernia who underwent preoperative esophageal manometry and either an open hernia repair with Collis gastroplasty and fundoplication (with Collis) or laparoscopic repair and fundoplication without Collis gastroplasty (without Collis) from 2005-2016. The MELH ratio was calculated by measuring the upper to lower esophageal sphincter distance divided by the patient's height. Results: Of 245 patients, 157 underwent repair with Collis, while 97 underwent repair without Collis. The Collis group had a shorter manometric esophageal length (20.2 vs. 22.4 cm, P <0.001) and lower MELH (0.12 vs. 0.13, P <0.001). The Collis group had fewer hernia recurrences (18% vs. 55%, log-rank P <0.001) and fewer reoperations for recurrence (0% vs. 10%, log-rank P <0.001) at 5 years. A 33% decrease in risk of hernia recurrence was seen for every 0.01 U increment in MELH ratio (hazard ratio: 0.67; 95% confidence interval: 0.55-0.83, P <0.001) while repair without Collis (hazard ratio: 6.1; 95% confidence interval: 3.2-11.7, P <0.001) was associated with increased risk of hernia recurrence. Conclusion: MELH ratio is an objective predictor of a shortened esophagus preoperatively. Lower MELH is associated with increased risk of recurrence and the risk associated with shortened esophagus can be mitigated with an esophageal lengthening procedure such as Collis gastroplasty.